A Modified Evaporation Model Indicates That the Effects of Air Warming on Global Drying Trends Have Been Overestimated. Issue 22 (22nd November 2021) - Liu, Meixian; Xu, Xianli; Scanlon, Bridget R.; Sun, Alexander Y.; Wang, Kelin
Abstract: Potential evapotranspiration (PET) is a key input to hydrologic models simulating the atmospheric water demand. Thus, uncertainties in PET would result in considerable uncertainty in model outputs. Among numerous PET algorithms, the Penman‐Monteith equation (PM equation) is most widely used because of its clear physical basis and acceptable estimation. However, PM equation has a physical limitation resulting from the linear approximation of the saturation water vapor pressure differences between the evaporation surface and the surrounding air, which can affect markedly the responses of PET to air warming. By considering a modified PM‐type evaporation model, we revisited the global drying trends based on the widely used Palmer Drought Severity Index (PDSI). We demonstrate that the studies, which based on the classic PM equation, often overestimate the effects of air warming on global drying trends. Particularly, the PET_PM (PET calculated using the classic PM equation) driven PDSI, overestimates global mean drought‐affected areas by 60%, drought intensity by 65%, and drought duration by 35% on average over the globe, and tends to overestimate drying trends in areas that are drying and underestimate wetting trends in areas that are becoming wetter. Key Points: Modifying PM evaporation model by introducing the nonlinear relationship between water vapor and temperature PM evaporation model overestimates the effects of air warming on potential evapotranspiration The drought index driven by PM‐type PET overestimates the global drying trends considerably